REVISING: SEXUALITY AND GENDER IN ARGENTINA’S LEFT-WING CULTURE IN THE EIGHTIES - López Perea, Fedra (Revista de Historia Social y de las Mentalidades, 2022)
During the 1980s, sectors of Argentina’s left-wing culture revised their recent history on both political and everyday terms, including sexual and gender aspects. Those revisions were guided by the notion that there was a “crisis of the left” and a need to redefine the characteristics of militancy.This took place in dialogue with the democratic opening and the “destape”. The magazines of the leftist culture acted as spaces where these debates unfolded, positions were presented and, in some cases, new propositions were laid out. This article reprises those debates that make it possible to observe changes in maters of gender and sexual dissidence in the left-wing culture in recent history.